10th AIAA/CEAS Aeroacoustics Conference 2004
DOI: 10.2514/6.2004-2929
|View full text |Cite
|
Sign up to set email alerts
|

Sound Generation in the Outlet Section of Gas Turbine Combustion Chambers

Abstract: Indirect combustion noise is investigated experimentally and numerically. This noise is generated in the outlet nozzle of combustion chambers if the entropy of the medium is nonuniform, which is the case in the exhaust of combustors. The contribution to the total noise emission of aeroengine combustors is not known. A test rig for the experimental investigation of this noise emission in the presence of swirl is first described. The indirect noise is generated in an exchangeable convergent-divergent nozzle at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The most simple model covering indirect combustion noise, and describing the transport of all possible modes of perturbation [2] in the wake of a flame, are the linearized Euler equations including anonisentropic energy equation supplemented by asource term to account for the instationary heat input [14],…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The most simple model covering indirect combustion noise, and describing the transport of all possible modes of perturbation [2] in the wake of a flame, are the linearized Euler equations including anonisentropic energy equation supplemented by asource term to account for the instationary heat input [14],…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Ap artially overlapping zonal approach based on aunsteady RANS simulation of the source zone wasfor example described by Schemel et al [14] using asponge layer to couple the perturbations from the CFD simulation into the propagation zone. An overviewonthe general procedure of applying CAA methods for the simulation of indirect combustion noise can be found in Schemel et al [14] and Richter and Thiele [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method revealed delay times from the internal combustor sensor to the far-field microphone, even though the correlated signal contained both periodic and random components. In addition, indirect combustion noise has been investigated numerically and with model-scale experiments by Schemel et al [32], Richter et al [33], and Bake et al [34][35][36].…”
mentioning
confidence: 98%
“…34 measured the cross spectra between temperature and pressure in a constant area duct downstream of a combustor and showed that the entropy fluctuations (hot spots) moved with the flow speed. Schemel et al (2004) 35 studied experimentally and numerically entropy noise generated by hot spots (from a combustor) passing through a nozzle. Richter et al (2005) 36 studied the application of computational aeroacoustic methods to indirect combustion noise generated by hot spots passing through a nozzle.…”
Section: Strahle Et Al (1977)mentioning
confidence: 99%